Methodical Competence of Teacher Trainees in Their Written Teacher Certification Examination - Bjedov Vesna (University of Maribor Press, 2013)
The paper discusses methodical competence of teacher trainees in their writtenpapers composed as part of their teacher certification examination. The aim ofthis discourse is to establish the existence of methodical competence of Croatianlanguage teacher trainees in their written teacher certification examination. Thepaper focuses on the following categories: the application of theoretical methodicalknowledge of basic sciences and special theoretical methodical knowledge,supporting theoretical knowledge and practical experience with examples, andfinding references in literature on methodology. The research was conducted on58 written papers of Croatian language teacher trainees in primary and secondaryschools in the following counties: Istria, Primorje-Gorski Kotar, Lika-Senj, Zagreb,Međimurje, Varaždin, Osijek-Baranja, Brod-Posavina, Požega-Slavonia, andVirovitica-Podravina. Based on this research study it was established that Croatianlanguage teacher trainees show methodical competence especially with regard tothe application of theoretical methodical knowledge of basic sciences and specialtheoretical methodical knowledge and references in literature on methodology.